An A to Z of common errors - Cumps, Jan, ....-; Philips, Diana, ....- (Antwerpen : Garant, 2015)
An A to Z of Common Errors is a handy and concise reference book enabling users to check tricky problems in the fields of grammar, vocabulary, pronunciation and spelling both quickly and easily.The explanations are phrased in simple, everyday language and are accompanied by clear examples, taken from newspapers and radio and TV broadcasts. An A to Z of Common Errors is a practical and easy to use guide which will be found most useful, not only by intermediate and advanced students of English, but indeed by all those whose professional activities require the use of English.